Mycoremediation of vinasse by surface response methodology and preliminary studies in air-lift bioreactors - Aragão, Moniky S. (2020)
This work evaluated the degradation of sugarcane vinasse with the production of biomass by Pleurotus sajor-caju CCB020, considering the combination of temperature and pH effects, using surface response methodology (RSM). A 22 complete central factorial composite experiment was used to analyze the results. The optimum temperature and pH values were respectively 27°C and 5.6 for maximum decolorization yield and 20°C and 6.8 for maximum biomass production. In parallel, scale-up experiments under conditions of 30°C and initial pH 5.0 were evaluated in two different air-lift bioreactors of 7.0L. Under these conditions, reductions of 53% and 58% in chemical oxygen demand (COD) and 71% and 58% in biological oxygen demand (BOD) were obtained respectively with the concentric tube type air-lift bioreactor with an increased degassing zone and without an increased degassing zone. Under these conditions, this study concluded that the systematic combination of P. sajor-caju and vinasse can be applied in the biodegradation process of refractory compounds contained in vinasse, concomitant to obtaining biomass and laccase and manganese peroxidase enzymes. Due to the good performance of the air-lift bioreactors, they can be used in scale studies in future industrial vinasse applications, besides it is possible to emphasize that different configurations in the bioreactor can affect the efficiency of the process.